The potential of the Council Presidency: An analysis of Germany's Chairmanship of the EU, 2007 - Daniela Kietz; Volker Perthes (Stiftung Wissenschaft und Politik (SWP), 2008)
By shedding light on the reasons for their success as well as identifying 'best practice', a critical dissection of EU presidencies can improve the functioning of the Union's Council system. The contributions to this study grapple with two questions, namely: what demands were placed on the German Council Presidency by different negotiating situations, and whether the Chair effectively and efficiently delivered on its different roles in the EU process. An object of particular attention is the processes and strategies by which the German Presidency adapted its performance to the demands it encountered.In order to generate broadly applicable recommendations, the contributions to the study systematically analyse the special resources available to the German government as well as the case-specific national contextual factors that helped define its scope for action. They also isolate the 'external' factors, beyond the Chair's influence, that facilitated - or hindered - its performance.Almost without exception, the contributions credit the German government with a solid performance in its management and brokerage roles, identifying a range of reasons for its success. These include a clear enunciation of its priorities, its resort to resource-intensive bilateral consultations, and the decisive commitment of the Federal Chancellor and Foreign Minister.The study closes with a critical look at the question whether the German modus operandi might be adopted by other presidencies. It then sets these developments in the context of the remoulding of the Council system set out in the Reform Treaty. The changes contained there will alter the working conditions of all presidencies from 2009
Keywords: 320